Entrepreneurial mindset and new venture creation: Evidence from Universiti Utara Malaysia (UUM) international students - Maiwada, Saminu (2015)
It is widely accepted that the issue of unemployment among the graduates is order of the day globally. Entrepreneurship addresses this issue through the creation of new ventures which have a significant influence on the world economic growth. The entrepreneurial spirit among the students in universities has been very low. There have been positive attempts to improve the role of university graduates as creators of new ventures. This study examined the entrepreneurial mindset and new venture creation among international students in Universiti Utara Malaysia (UUM). This study finds very distinct support of entrepreneurial orientation, entrepreneurship perception and university’s role as the factors that influence new venture creation among the international students. The study employed a cross sectional approach with the use of survey questionnaires in collecting data. A total of 273 responses were analyzed using multiple regressions analysis. The results indicated that there are positive relationships between all the variables.